FRI0510 Increased expression of v-domain ig suppressor of t-cell activation (VISTA) on leukocytes of granulomatosis with polyangiitis (GPA) patients. (12th June 2018) - Hid Cadena, R.; Yuan, J.; Huitema, M.G.; Boots, A.M.; Stegeman, C.; Brouwer, E.; Rutgers, A.; Heeringa, P.; Abdulahad, W.H.
Abstract : Background: Vascular inflammation in GPA is the result from an inflammatory event combined with a highly specific immune response. Antineutrophil cytoplasmic antibodies (ANCA) specific for GPA are directed against neutrophil granule proteins. Neutrophils are known to play an important role in the pathogenesis of GPA. Under normal conditions, activation of immune cells is positively and negatively regulated by stimulatory and inhibitory checkpoint molecules. The right balance between the expression of both molecules is crucial in fine-tuning the immune response and preventing autoimmunity. Recently, VISTA (V-domain Ig suppressor of T cell activation) has been identified as a potent negative regulator of T cell activation. Objectives: This study aimed to investigate the expression of VISTA on circulating leukocytes of GPA-patients and compare it with vasculitis control (VC) patients with Giant Cell Arteritis (GCA) and healthy controls (HC). Methods: In a cross-sectional study, fresh blood samples were obtained from 43 GPA-patients in remission on immunosuppressive treatment, 24 VC and 34 sex and age-matched HC. The frequency of VISTA expression was determined on Th-cells (CD45RO - and CD45RO + ), NK cells, monocyte subsets (classical/non classical/intermediate) and on neutrophils (suppressive/non suppressive subsets) by flow cytometry. Results: The proportion of VISTA expressing Th-cells was significantly increased in GPA-patients compared with HCs, this increase could be seen in both, the CD45RO - compartment as well as in the CD45RO + compartment. NK cells from GPA-patients showed an increase in the proportion of VISTA expressing cells when compared to the VCs and HCs. Among monocyte subsets, a slight decrease in the proportion of VISTA on the Intermediate subset could be seen. Interestingly, on neutrophils a significant increase in the proportion of VISTA + cells was seen in GPA-patients in comparison to HCs and VCs. This increase was most pronounced in the suppressive neutrophil subset. Conclusions: VISTA expression is increased in both naïve and memory Th cells of GPA patients in remission. Interestingly, neutrophils of GPA patients showed higher levels of VISTA and this was most pronounced in the suppressive neutrophil subset. Whether the increased expression of VISTA has functional consequences needs further investigation. Disclosure of Interest: None declared